REPORT OF THE COMMITTEE ON THE CPA EXAMINATION: APPRAISAL OF THE CONTEXT OF THE CPA EXAMINATION. - Bannon, Richard J.; Germain, Evroul S.; James, Foster W.; Kohler, Paul A.; Moss, Morton F.; Horngren, Charles T. (The Accounting Review, 1962)
During the last two decades, the demand for the services of the Certified Public Accountant (CPA) has expanded at an astonishing rate. Such favorable recognition, however, imposes greater responsibility upon the profession to maintain high standards for admission to its ranks. One of the essential characteristics of a profession is a body of special knowledge. Every candidate for admission to the profession should be required to prove his mastery of the common core of knowledge that all CPAs should possess. This article presents the report of the Committee on the CPA examination. The report presented the results of the committee's study and evaluation of the content of the CPA examination in relation to its basic objective. The report was presented in three major parts–A statement of the knowledge and abilities, which a CPA should possess together with an analysis of what knowledge the CPA examination should test, an evaluation of specific subject matter of the CPA examination, and conclusions. The points discussed in the report include–General knowledge: what the examination should not test, commercial law should be deleted, need for a description of the Common body of knowledge, special knowledge: what the Examination should test, scope of management services, taxes, accounting theory, accounting practice, and auditing. The report concludes that the proper objective of the CPA examination is to test the common body of special knowledge that all CPAs should possess.